LE CENTRE UNIVERSITAIRE MEDITERRANEEN ENTRE 1933 ET 1939: DE LA CREATION A LA VEILLE DE LA SECONDE GUERRE MONDIALE - Jemai, Slim (مركز الدراسات والابحاث الاقتصادية والاجتماعية, 2008)
The Mediterranean University Center (the C.U.M) is an organization of higher education specialized in the study and the dissemination of the Mediterranean culture. The period here studied extends from 1933 (C.UM’s foundation year) to 1939, in a difficult historical context marked by the consequences of the First World war, international tensions and the consequences of the world economic crisis 1929. At the time the Nice region faces the collapse of luxury tourism and a substantial increase of unemployment. Between 1933 and 1939 the municipal life in Nice is dominated by the personality of Jean Medecin who, with Paul Valery (first administrator of the C.UM) and other personalities, plays a major role in the foundation of the C.U.M in 1933. Once created, the C.U.M meets a great public success. It aims for the cultural enrichment of the city of Nice and of the Mediterranean region.
Keywords: جامعة البحر المتوسط -- الحرب العالمية الثانية